Grow-out Production of Pabda (Ompok bimaculatus) in Earthen Ponds under Low Stocking Density - Debnath, Chandan; Sahoo, Lopamudra; Yadav, Gulab Singh; Datta, M.; Ngachan, S. V. (Indian Journal of Hill Farming, 2016)
The growth and survival of Ompok bimaculatus (pabda) was evaluated in earthen ponds (0.03 ha; 1.0 m) over a period of 6 months under low stocking densities to see its production potential. The fish were stocked at the rate of 4000 (T1), 5000 (T2) and 6000 fingerlings ha-1 (T3). During stocking, all the fish were of same age group with an average size of 3.36±0.08cm in length and 0.83±0.02g in weight. The fish were fed on formulated feed (18% CP) daily at 2 to 4% of biomass. After 6 months, the fish grew to a size of 64.66g in T1, 65.66 g in T2 and 65.33g in T3 which was not significantly different (p≥0.05). The production of the fish was 295.07 kg ha-1 in T3, 247.26 kg ha-1 in T2, 197.26 kg ha-1 and significantly different (p≤0.05). The survival of the fish was 76.23% in T1, 75.33% in T2, 75.26% in T3 and significantly different (p≤0.05). Feed conversion ratios in T1 (2.2), T2 (2.3) and T3 (2.2) were not significant different (p≥0.05). Water and soil quality parameters and plankton showed normal fluctuations and remained within the ranges suitable for fish culture. The study concluded with the recommendation that there is scope for enhancing the production of pabda through stocking fingerlings exceeding 6000 ha-1.